Scalable, Durable, and Recyclable Metal‐Free Catalysts for Highly Efficient Conversion of CO2 to Cyclic Carbonates - Zhang, Yao‐Yao; Yang, Guan‐Wen; Xie, Rui; Yang, Li; Li, Bo; Wu, Guang‐Peng (Angewandte Chemie International Edition, 2020)
A series of highly active organoboron catalysts for the coupling of CO2 and epoxides with the advantages of scalable preparation, thermostability, and recyclability is reported. The metal‐free catalysts show high reactivity towards a wide scope of cyclic carbonates (14 examples) and can withstand a high temperature up to 150 °C. Compared with the current metal‐free catalytic systems that use mol % catalyst loading, the catalytic capacity of the catalyst described herein can be enhanced by three orders of magnitude (epoxide/cat.=200 000/1, mole ratio) in the presence of a cocatalyst. This feature greatly narrows the gap between metal‐free catalysts and state‐of‐the‐art metallic systems. An intramolecular cooperative mechanism is proposed and certified on the basis of investigations on crystal structures, structure–performance relationships, kinetic studies, and key reaction intermediates. A highly active bifunctional organoboron catalyst with the advantages of scalable preparation, thermostability, and recyclability was reported for the cyclization of CO2 and epoxides. An intramolecular cooperative mechanism was substantiated by investigations into the crystal structure of the catalysts, structure– performance relationships, kinetic studies, and the key reaction intermediates.